Synthesis of Orthogonally Protected 2,6-Diazaspiro[3.5]nonane and 2,6-Diazaspiro[3.4]octane Analogues as Versatile Building Blocks in Medicinal Chemistry - Orain, David; Hintermann, Samuel; Pudelko, Maciej; Carballa, Diego; Jedrzejczak, Anna (Synlett, 2015)
A novel and efficient synthesis of orthogonally protected spirocyclic amines is described for the first time.
Keywords: spirocyclic amine; 2,6-diazaspiro[3.5]nonane; 2,6-diazaspiro[3.4]octane; azetidine deprotection; orthogonal protecting groups